INTEGRATING CHARACTER EDUCATION IN THE ENGLISH TEACHING AT ISLAMIC JUNIOR HIGH SCHOOLS IN INDONESIA - Milal, A. Dzo’ul; Rohmah, Zuliati; Kusumajanti, Wahju; Basthomi, Yazid; Sholihah, Diana Nur; Susilowati, Meinarni (TEFLIN Journal, 2020)
The rapid development of digital technology with its likely disruptive impacts on students’ morality and character necessitates teachers to reorient their roles. Teachers need to be skillful in incorporating moral messages and character education in their teaching supported by suitable learning resources. The current research is conducted to fulfill the needs of the English teachers in Islamic junior secondary schools in Indonesia for supplementary materials that can support the integration of Islamic moral messages and values in the teaching of English. These needs were identified from data collected through questionnaires, FGDs, and interviews. The supplementary materials, which were designed based on the needs analysis, underwent expert validation and a pilot study. The final version of the materials consists of ready-to-use-worksheets and teacher’s guide and is named the Islamic Life Resource Pack (ILRP).